Contract Enforcement in Platform-Based Hospitality Channels: A Transaction Cost Economics Perspective - Aprillia Elly Kusumastuti; Setyo Pantawis (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study examines the role of contract enforcement in shaping marketing channel performance in B2B hospitality partnerships. It investigates the effects of contract enforcement on opportunistic behavior and cooperative channel performance, as well as the moderating role of cohesive collectivism in the relationship between contract enforcement and opportunism. Research Design & Methods: The quantitative research design used a questionnaire to 103 owners and managers of online accommodation providers in Central Java. Data were analyzed using PLS-SEM. Findings: From a TCE perspective, the findings affirm the dominance of formal governance mechanisms in controlling exchange hazards. Contract specificity enhances contract enforcement and cooperative channel performance by reducing opportunism. The absence of a moderating effect of Cohesive collectivism constitutes an important theoretical contribution, indicating that in standardized, platform-based B2B partnerships, opportunism is more effectively governed through legal and contractual mechanisms than through social cohesion. This clarifies the limited role of relational mechanisms and reinforces the relevance of TCE in explaining governance efficiency in market-oriented exchanges. Implications & Recommendations: The results support TCE by demonstrating that effective contract enforcement reduces transaction costs, enhances institutional efficiency, and strengthens coordination in digital hospitality channels. Formal contractual mechanisms play a critical role in ensuring legal certainty, controlling opportunism, building trust, and sustaining long-term cooperation among platform-based partners. Contribution & Value Added: This study contributes to the B2B marketing and channel management literature by emphasizing the dominance of formal governance mechanisms over social dynamics in mitigating opportunistic behavior in platform-mediated hospitality networks.